Pall helps bring clean water to remote Haitian village. Issue 10 (October 2015) - Unknown
Abstract : The Aria water filtration system from US filtration, separation and purification company Pall is providing clean drinking water to residents of Grande-Saline, a remote village in north-west Haiti.